A Study Of The Circulation Of Covid-19 Viruses Flow In A Particular Space - Shukri, Mohamad Akmal Mohd (Universiti Sains Malaysia, 2021)
COVID-19 pandemic situation have been ongoing for almost two years now, and the infection cases is not showing any sign of stopping just yet. Thus, it is very important for the scientists, engineers, and researchers alike to continue the comprehensive study to find both the cures and the most effective prevention method to help mitigate the continuous infection cases of COVID-19 viruses among the people. Studying the circulation of COVID-19 viruses flow in a particular space is necessary to further understand the spreading mechanism of the viruses. Therefore, this research aims to utilize the computational fluid dynamic (CFD) simulation software which is Ansys Fluent, to developed and simulate an effective model of cough mechanism of individuals infected with COVID-19 and the particles releases alongside the cough jet inside a confine space to study the behaviour of the particles and track their movement. The final results of this research concluded that, the cough droplets from infected person consist of two types of droplets, namely respiratory droplets (5μm to 10μm size) and droplets nuclei or aerosols (smaller than 5μm). Based on the conducted simulation, the spreading pattern of coarse respiratory droplets is highly directional, that is it follows the direction of the infected person cough jet. The aerosols however, would be greatly affected by the airflow and it’s turbulence in a space. The most effective way to avoid the transmission of COVID-19 viruses through respiratory droplets is through avoiding sitting or standing in front of infected person if the person are performing any vigorous respiratory activity such as heavy breathing, coughing or sneezing. To prevent the viruses spread through aerosols, careful planning of air ventilation and practicing wearing face mask would be the most effective method to prevent inhalation of the viruses possibly present inside the space.